2020
DOI: 10.1002/oby.22779
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent High‐Fat Diet Intake Reduces Sensitivity to Intragastric Nutrient Infusion and Exogenous Amylin in Female Rats

Abstract: Objective: Intermittent (INT) access to a high-fat diet (HFD) can induce excessive-intake phenotypes in rodents. This study hypothesized that impaired satiation responses contribute to elevated intake in an INT-HFD access model. Methods: First, this study characterized the intake and meal patterns of female rats that were subjected to an INT HFD in which a 45% HFD was presented for 20 hours every fourth day. To examine nutrient-induced satiation, rats received intragastric infusions of saline or Ensure Plus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Indeed, most published work on the effects of mesolimbic amylin receptor signaling for energy balance control has examined responses exclusively in male subjects ( Mietlicki-Baase et al, 2013 , 2015 , 2017 ). The effects of amylin on feeding and weight control in females remains an active area of investigation ( Roth et al, 2007 ; Asarian and Geary, 2013 ; Maske et al, 2020 ), and it will be important in future work to determine whether VTA amylin receptor activation in females produces similar effects on NAcC DA responses to nutrient stimuli. It will also be informative to evaluate the influence of the estrous cycle on the effects of amylin signaling, because estrogens can exert both within-cycle and chronic effects on the ability of amylin to suppress feeding ( Trevaskis et al, 2010 ; Asarian and Geary, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most published work on the effects of mesolimbic amylin receptor signaling for energy balance control has examined responses exclusively in male subjects ( Mietlicki-Baase et al, 2013 , 2015 , 2017 ). The effects of amylin on feeding and weight control in females remains an active area of investigation ( Roth et al, 2007 ; Asarian and Geary, 2013 ; Maske et al, 2020 ), and it will be important in future work to determine whether VTA amylin receptor activation in females produces similar effects on NAcC DA responses to nutrient stimuli. It will also be informative to evaluate the influence of the estrous cycle on the effects of amylin signaling, because estrogens can exert both within-cycle and chronic effects on the ability of amylin to suppress feeding ( Trevaskis et al, 2010 ; Asarian and Geary, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that binge-like eating over several weeks in a model of intermittent fat feeding in rats affects the GLP-1 system, decreasing PPG mRNA expression in the NTS, suggesting downregulation of central GLP-1 signaling [265], accordingly with dysfunction in satiation processes that generally serve to limit food intake observed in different animal models [265]. Moreover, rats with intermittent access to a high-fat diet show large meals [266] and reduced responsiveness to intragastric nutrients and amylin, supporting the idea of reduced sensitivity to satiation signals under these conditions [266]. A possible loss of sensitivity to GLP-1 is not yet proven and could also explain the lack of inhibition of large meals observed in this animal model.…”
Section: Stress In Obesity: Glp-1 and The Motivation To Feedmentioning
confidence: 99%